A Comparative Analysis of Metaphors in ‘Rearrange My World’ By Daniel Cesar and Rex Orange County Using Lakoff and Johnson’s and Goatly’s Theories - Diah Resmisari; Yosephine Dinda; Susari Nugraheni; Mukhlasul Fasikh (JELL (Journal of English Language and Literature) STIBA-IEC Jakarta, 2026)
This study examines the use of metaphorical language in the song ‘Rearrange My World’ by Daniel Caesar and Rex Orange County using two analytical approaches: Conceptual Metaphor Theory proposed by (Lakoff & Johnson, 1980) and Goatly’s rhetorical classification of metaphor (1997). The study aims to identify metaphorical expressions in the song and examine their general meanings as well as differences in interpretation across the two frameworks. The findings reveal eight metaphorical expressions, which are classified into structural and ontological metaphors under Conceptual Metaphor Theory. Based on Goatly’s classification, the same expressions are categorised as active, inactive, subjective, asymmetric, and dead metaphors. The analysis shows that the metaphors in the song represent emotional experiences by mapping abstract concepts onto concrete domains such as movement, objects, and space. By applying both frameworks, the study demonstrates that metaphor functions not only as a cognitive mechanism for structuring abstract experience but also as a rhetorical device that shapes emotional expression in song lyrics. Overall, the findings confirm that metaphor plays a central role in meaning-making in contemporary popular music